Pituitary Non-Functioning Adenoma Disclosed at 18F-Choline PET/CT to Investigate a Prostate Cancer Relapse. (October 2016) - Maffione, Anna Margherita; Mandoliti, Giovanni; Pasini, Felice; Colletti, Patrick M.; Rubello, Domenico
Abstract : Abstract: We report the incidental finding of a pituitary macroadenoma on an 18 F-choline PET/CT in a patient with recurrent prostate cancer. The pituitary gland was clearly enlarged and intensely FDG avid (SUVmax, 6.6). The diagnosis was confirmed by a subsequent contrast-enhanced MR evaluation, and the macroadenoma was classified as nonfunctioning on the basis of normality of the specific serum hormonal profile. A follow-up 18 F-choline PET/CT scan performed after 6 months revealed stable dimension, and uptake of the pituitary macroadenoma patient deceased 1 month later. At autopsy, intracytoplasmic vesicles containing growth and prolactin hormones were observed at immunohistochemistry.